The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.energy.2013.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Top management and the adoption of energy efficiency practices: Evidence from small and medium-sized manufacturing firms in the US

Abstract: a b s t r a c tBarriers to energy efficiency have been extensively discussed in the energy literature, but little is known about positive drivers. This paper investigates the role of top managers and more specifically of top operations managers on the adoption of energy-efficiency practices, based on 5779 energy efficiency recommendations made to 752 small and medium-sized manufacturing firms under the US Department of Energy's IACs (Industrial Assessment Centers) Program, through which teams of students and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 57 publications
5
70
1
4
Order By: Relevance
“…Moreover, Anderson, De Dreu, and Nijstad [58] revealed that firms are about 40% more responsive to investment costs than to energy savings (operating costs). In fact, energy efficiency investments have a larger probability of being realized if the payback time is shorter than 2-3 years [72,86,87]. Thus, we identified contradicting research results considering the economic rationale that drives energy efficiency.…”
Section: Economic Driverscontrasting
confidence: 48%
“…Moreover, Anderson, De Dreu, and Nijstad [58] revealed that firms are about 40% more responsive to investment costs than to energy savings (operating costs). In fact, energy efficiency investments have a larger probability of being realized if the payback time is shorter than 2-3 years [72,86,87]. Thus, we identified contradicting research results considering the economic rationale that drives energy efficiency.…”
Section: Economic Driverscontrasting
confidence: 48%
“…Gordić et al, 2010;Virtanen et al, 2013), whereas the studies which focus on SME mainly applied a quantitative or mixed method design (e.g. Önüt & Soner, 2007;Blass et al, 2014). Figure 6 illustrates the industry sector distribution of the analyzed studies.…”
Section: Study Methodologiesmentioning
confidence: 99%
“…Based on a sample of 752 small and medium-sized U.S. manufacturing firms, Blass et al (2014) empirically investigate the role of top managers in the adoption of energy-efficiency practices. They find that the involvement of top operations managers with a clearly operationally-focused position significantly increases the adoption of energy-efficiency initiatives, while involvement of general top managers without an operational role has little or no effect.…”
Section: Culturementioning
confidence: 99%
See 1 more Smart Citation
“…From the standpoint of a systemic and integrated approach the authors fully explore the problem of energy management development at the level of enterprises and companies, the private moments, such as energy auditing survey and the development of energy efficiency programs, which are paid more attention to the practice [7,8,9,10,11,12,13].…”
Section: The Theoretical Rationale Of Tool Development Expediency Of mentioning
confidence: 99%